Analisis Solusi Masalah Perambahan di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Diklat Sisimeni Sanam - Alexander Alfa Jan Junior Seran; Wilhelmina Seran; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This study aims to determine the main factors causing forest encroachment that occurred in the Special Purpose Forest Area (KHDTK) Education and Training Forest of Sisimeni Sanam. The method used in this study is a non-probability sampling method for two groups of informants, namely general public and the officers of KHDTK Sisimeni Sanam. The sampling technique for general public used the snowball sampling method while for the officers used the purposive sampling method. Data were analyzed using Miles & Huberman model of data analysis which includes data reduction, data presentation and verification. The results showed that there are three dominant factors causing encroachment in KHDTK Sisimeni Sanam, they are economic factors, soil fertility factors and limited land area, and tenure conflict factors. The formulation of the solution to these encroachment problems is to increase cooperation and collaboration with the community in managing land in the area by increasing the number of Forest Farmer Groups (KTH), conducting regular and intense socialization to all community members living in and around the area, assistance and regulate land cropping patterns in the area, conducting complete and clear data collection on the people living in the area, giving appreciation to the people who guard and protect the area, increase the number of security officers or increase the number of community members as security guards in each area, optimizing land management with an agroforestry system, and making village regulations (PerDes) which regulate encroachment in each village